Bacteriuria in pre- and post urethral catheterization of cats with obstructive lower urinary tract disease - Phoon, Melissa Hoi Ee; Dhaliwal, Gurmeet Kaur; Lau, Seng Fong; Khor, Kuan Hua (2015)
Urethral obstruction diagnosed in lower urinary tract disease of cats (FLUTD) is a life-threatening emergency. The standard treatment for urethral obstruction is urethral catheterisation aimed to re-establish urethral patency. However, there is always a concern of ascending bacterial infections. Additionally, the routine use of antibiotics are not recommended while the catheter is in place, as studies in the West have shown that only 2-5 % of cats with obstructed FLUTD are due to bacterial causes. This study was designed to determine the prevalence of bacterial cystitis in cats presented with obstructive FLUTD and to investigate the prevalence of bacterial infections associated with urethral catheterisation in cats presented with urethral obstruction between January to April 2014 at University Veterinary Hospital, University Putra Malaysia (UVH-UPM). Urine samples were obtained by cystocentesis upon admission before catheterisation and via mid-collection of urine from the urinary catheter on day 3 post-catheterisation for bacterial culture. In this study, 28.9% (n=4/14) of cats with obstructive FLUTD were presented with bacteriuria. There was a significant increase (P=0.008) in incidence of bacteriuria at Day 3 post-relief of urethral obstruction, compared to the pre-relief group. The most common bacteria cultured were Escherichia coli and Klebsiella pneumonia. The presence of bacteria in cats with FLUTD is higher than others reported in the West. Catheterisation does increase the risk of urinary tract infections. Thus a urine bacterial culture is recommended post catheter removal. The use of antibiotics, if required, should commence after removal of the catheter.